Transformational leadership, affective commitment with Organizational citizenship behavior mediation to employee performance - Agung Permana Putra; Laura Syahrul; Hendra Lukito (Enrichment : Journal of Management, 2023)
In this study, it was conducted to determine the effect of transformational leadership and affective commitment on employee performance with organizational citizenship behavior as a mediating variable. This research was conducted at the Community and Village Empowerment Office of West Sumatra Province. The independent variables in this study are transformational leadership and affective commitment and organizational citizenship behavior as mediating variables while employee performance is used as the dependent variable. Sampling technique with probability samples. So that the population of respondents used as many as 105 employees. The analytical method used is descriptive statistical analysis and inferential analysis using SmartPLS 3.0. The results of the research show that transformational leadership has no effect on employee performance; affective commitment has no effect on employee performance; organizational citizenship behavior affects employee performance; transformational leadership influences organizational citizenship behavior; affective commitment affects organizational citizenship behavior; then organizational citizenship behavior as a mediating variable affecting transformational leadership on employee performance; and organizational citizenship behavior as a mediating variable affecting affective commitment to employee performance.